(untitled) (Emergency Care Journal, 2018)
Platypnea-orthodeoxia syndrome (POS) is an unusual cause of hypoxia characterized by enormous variation in oxygen saturation during postural changes. We describe here the clinical presentation, the diagnostic challenge of POS and discuss the main pathophysiological etiologies of the disease in a 75-year-old woman who was admitted because shortness of breath. After ruling out the most important causes of dyspnea we observed that the symptoms improved when the patient was lying flat. The diagnostic workup with computed tomography scan and air bubble saline echocardiography lead us to a correct diagnosis.